The diplomatic traditional for diplomatic contemporary: trajectory and convergence with the archival science - Nascimento, Maiara de Arruda (2016)
This article discusses the path taken by the Diplomatic from its origin when its purpose was to prove the authenticity of medieval documents, to the present time, in dealing with documental genesis, in other words, the study of how the documents appear in for entities that produced them. This is a literature search, the type of literature review, which was to supply the national and international literature available in journal articles, books and theses. It presents the history, the concepts and the contribution of the Diplomatic for archiving, as by providing subsidies for the analysis of the elements of the documents, the Diplomatic can contribute to the understanding of the document together as an organic whole. Thus concludes that the Diplomatic is an important tool to be appropriate for archiving, and the purpose of the processing of documentary collections, encompassing the various documents produced today, including digital.